Lotus 1-2-3 versi 2.4 WYSIWYG Lotus for windows - Goh, Ong Sing; Ahmad, Z. (Pustaka Aman Press, 1995)
A main goal of this book was to create utilities for Lotus 1-2-3 spreadsheet that will make a reader to understand and used WYSIWYG Lotus for Windows. The objective of this book is to make it easier to use the spreadsheet.